Financial inclusion among small agribusiness entrepreneurs in Northern Nigeria - Adamu, Idris Yahaya (2018)
Financial inclusion is considered an effective strategy to enhance the development of small agribusiness entrepreneurs. However, previous literature does not provide unified, comprehensive indicators and requirements that ascertain the extent of financial inclusion, the banks’ approach to implementing financial inclusion, the process of giving out financing and small agribusiness entrepreneurs’ challenges towards enhancing financial inclusion. This study identified indicators and requirements for financial inclusion, banks' approaches to implementing financial inclusion, banks' process of giving out financing, and challenges faced by small agribusiness entrepreneurs to strengthen financial inclusion in Northern Nigeria. The study used qualitative approach and purposive sampling strategy through in-depth interviews and content analysis to explore experiences of informants about financial inclusion. The study identified comprehensive indicators and requirements that determine and enhance financial inclusion. Banks implement financial inclusion by ensuring access to savings, payments, and credit. Additionally, banks promote consumer protection, financial literacy, and Know Your Customer (KYC) compliance. Islamic and conventional banks' approaches in implementing financial inclusion are the same, except in the financing process. Banks are careful in lending/financing due to challenges of borrowers' repayment capacity. However, banks follow flexible and all-inclusive means to extend lending/financing. Jaiz bank relies more on debt-based financing to enhance financial inclusion. Small agribusiness entrepreneurs face challenges of loan security, investments viability and increasing cost of financing. This study identifies banks' impact on small agribusiness entrepreneurs' inclusion and shows the function and role of banks towards the financial inclusion drive. The study increases entrepreneurs' awareness of financial services and Islamic banking. Banks may use this study to predict clients' challenges and financing needs. With this study, banks could help financial regulators to redesign strategies towards Islamic banking, credit, outreach, and financial literacy.